A la recherche de l'intérêt européen (Paris, 2008)
"Economists, civil society actors, European Commission’s high level officers, they are all committed to and fascinated by Europe. They here set the discusssion framework: the European Union must undertake deep changes so that citizens can identify the meaning and the positive contributions of its policies. 18 major articles to enable the European Union to become a full global actor. A useful book for decision-makers and citizens of Europe."